Treatment modality impact on quality of life for human papillomavirus–associated oropharynx cancer. (27th March 2019) - Xu, Mary Jue; Plonowska, Karolina A.; Gurman, Zev R.; Humphrey, Amanda K.; Ha, Patrick K.; Wang, Steven J.; El‐Sayed, Ivan H.; Heaton, Chase M.; George, Jonathan R.; Yom, Sue S.; Algazi, Alain P.; Ryan, William R.
Abstract : Objectives/Hypothesis: Compare treatment‐related quality of life (QOL) impact for early‐stage human papillomavirus–associated oropharynx squamous cell carcinoma (HPV+ OPSCC) patients. Study Design: Retrospective cohort at a tertiary center. Methods: Stage I (T0‐2/N0‐1) HPV+ OPSCC patients (n = 76) with pretreatment Karnofsky scores ≥80 reported QOL after surgery alone (n = 17, 22%), surgery with adjuvant radiation ± chemotherapy (S‐a[C]XRT) (n = 23, 30%), or definitive radiation ± chemotherapy (d[C]XRT) (n = 36, 47%) with the University of Washington QOL version 4 (UW‐QOL); European Organization for Research and Treatment of Cancer Quality of Life Questionnaire, Core Module (EORTC QLQ‐C30) and Head and Neck Module (EORTC QLQ‐HN35); University of Michigan Xerostomia, and Neck Dissection Impairment Index questionnaires (median follow‐up = 2.2 years, interquartile range = 1.0–4.2 years). Treatment adverse events and gastrostomy tube rates were assessed. Results: Over 87% of each treatment group reported good or better overall QOL. Each group had low gastrostomy tube and treatment‐specific complication rates. S‐a(C)XRT and d(C)XRT patients had similar mean scores with wide ranges for most individual and all composite categories. S‐a(C)XRT compared to d(C)XRT patients reported significantly fewer dental problems (EORTC QLQ‐C30/HN35 means = 10.1 vs. 34.3, P = .007), worse appearance (UW‐QOL means = 72.8 vs. 82.6, P = .02), and worse coughing (EORTC QLQ‐C30/HN35 means = 31.9 vs. 15.7, P = .007). Surgery alone compared to d(C)XRT and S‐a(C)XRT patients reported significantly better salivary/taste/oral functions and less pain, financial, oral/dental, and sexual problems. Conclusions: For early‐stage HPV+ OPSCC, patients usually achieve acceptable QOL regardless of treatment. S‐a(C)XRT and d(C)XRT patients report generally similar QOL including neck/shoulder pain/function, but with a wide range in a limited patient sample. Surgery alone should be considered, when oncologically and functionally safe, given the better associated QOL. Level of Evidence: 4 Laryngoscope, 130:E48–E56, 2020